CIRCUMSTELLAR ALUMINUM OXIDE AND SILICON CARBIDE IN INTERPLANETARY DUST PARTICLES - Stadermann F.J.; Floss C.; Wopenka B. (My University, 2006)
A systematic NanoSIMS isotope imaging study of sub-micrometer phases in interplanetary dust particles (IDPs) has led to the discovery of two presolar grain types that previously were observed only in primitive meteorites. A 350 ? 600 nm2 Al2O3 grain has a large 17O enrichment and a slight 18O depletion, as well as a 26Mg excess due to the decay of extinct 26Al. Because of its relatively large size and prominent location within the IDP, this presolar Al2O3 grain is well characterized by SEM-EDX analyses. A second, much smaller presolar grain has a diameter of 150 nm and a 13C enrichment of more than 300%. Isotopic anomalies in C are rarely found in IDPs and the magnitude of this anomaly is unprecedented. This grain also has a 15N-rich composition and its isotopic makeup as well as its secondary ion yields identify it as a SiC grain. The discovery of presolar Al2O3 and SiC in IDPs seamlessly complements earlier notions of interplanetary dust particles as the most primitive extraterrestrial material currently available for laboratory analysis. Both Al2O3 and SiC are common presolar grain types in primitive meteorites, but they appeared conspicuously absent from the presolar grain inventory in interplanetary dust particles, which is dominated by silicate stardust. Not finding these presolar grain types in interplanetary dust would have been difficult to explain. Abundance estimates of the new presolar grain types in IDPs are hampered by limited statistics, but both Al2O3 and SiC are less common than presolar silicates which have been found at relatively high abundances in IDPs. The particle in which these presolar grains have been found belongs to the ’isotopically primitive subgroup’ of IDPs, yet does not contain any presolar silicates.
Keywords: ALUMINUM OXIDE; IMAGING METHOD; INTERPLANETARY DUST; SCANNING ELECTRON MICROSCOPY